Growth Response and Yield of Pagoda Mustard Plant (Brassica narinosa) Due to Concentration and Time Interval of Liquid Bokashi Administration of Rice Washing Water - Ida Sugeng Suyani; Mimik Umi Zuhroh (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the growth response and yield of pagoda mustard (Brassica narinosa) due to the concentration and time interval for applying liquid bokashi to rice washing water. The research was conducted from December 2019 to February 2020 in Lumbang Village, Lumbang District, Probolinggo Regency. This study used a factorial randomized block design method with two factors, namely concentration and time interval for giving liquid bokashi rice washing water 3 times. The treatment consisted of 2 factors. The first factor is the concentration of liquid bokashi rice washing water (K), namely: K0 = 0% (control/without giving liquid bokashi. The second factor is the time interval for giving liquid bokashi (L). Observation variables consist of plant height (cm), number of leaves (fruit), leaf area (cm2), wet stover weight (g), dry stover weight (g), root length (cm), In this study using a linear model. Data will be analyzed by means of the F test, If the factor variance If there is a significant effect on the interaction, it is tested with 5% DMRT. The conclusions of this study are 1). The concentration of liquid bokashi had a significant effect on the parameters of plant height, number of leaves, leaf area, wet stover weight, dry stover weight and root length, 2). The time interval for bokashi administration had no significant effect on all observation parameters, 3). administration of liquid bokashi and time interval of administration on the growth and yield of pagoda mustard in almost all observed parameters.